Clinicopathological Features of Inflammatory Myofibroblastic Tumor in the Breast - Shifei Liu; Rui Yuan; Yulan Jin; Chunyan He; Xingzheng Zheng; Yang Zhan (The Breast Journal)
Inflammatory myofibroblastic tumor (IMT) is a mesenchymal spindle cell tumour with low malignant potential which is extremely rare in breasts. Because of the lack of typical imaging and clinical characteristics of IMT, it is easy to misdiagnose before operation. We now report a case of a 37-year-old woman presenting with a mass in her left breast. Ultrasound showed a well-circumscribed lesion in the lower outer quadrant. The patient underwent lumpectomy, and histopathology revealed a tumor which was composed of fusiform cells and inflammatory cells. Immunohistochemistry (IHC) showed tumor cells are positive for vimentin, ALK, BCL2, and SMA. The FISH test demonstrated ALK (2p23) chromosomal translocation (ALK positive). The final diagnosis of breast IMT was rendered with nonclassical morphology. Postoperative 30-month follow-up no evidence showed residual tumor or recurrence. As a very rare tumor, breast IMT could be easily misdiagnosed clinically and pathologically. Complete surgical resection of the tumor is preferred, and it has the risk of recurrence and metastasis.